2020
DOI: 10.5045/br.2020.2020080
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations in chronic lymphocytic leukemia and their correlation with clinico-hematological parameters and disease progression

Abstract: Background Chronic lymphocytic leukemia (CLL) is a heterogeneous disease, which is attributed to differences in the genetic characteristics of the leukemic clone. We studied the genomic profile of 52 treatment-naïve CLL patients. Methods Genetic analysis was performed by multiplex ligation-dependent probe amplification (MLPA) using the SALSA P038 Probemix (MRC Holland, Amsterdam), which contains probes for 2p (MYCN,ALK,REL), 6q, 8p (TNFRSF10A/B), 8q (EIF3H,MYC), 9p21 (CDKN2A/B), 10q (PTEN), 11q (ATM, RDX, PPP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
4
1
1
Order By: Relevance
“…The male to female ratio in the control and CLL groups was 2:1 in the current study, with no significant difference between the two groups, which is similar to another conclusion from another study that mentions a comparable statistical ratio (1.8:1,1.5:1 respectively) (13) .…”
Section: Discussionsupporting
confidence: 91%
“…The male to female ratio in the control and CLL groups was 2:1 in the current study, with no significant difference between the two groups, which is similar to another conclusion from another study that mentions a comparable statistical ratio (1.8:1,1.5:1 respectively) (13) .…”
Section: Discussionsupporting
confidence: 91%
“…These mutations are recently identified as CLL disease parameters. The presence of these mutations is associated with at least one unfavorable prognostic marker [30][31][32][33]. However, these mutations were not detected in any of our patients.…”
Section: Discussioncontrasting
confidence: 50%
“…In this signature which consisted of nine prognostic lncRNAs related to redox genes, COLCA1 has been reported and identified as a key lncRNA in colorectal cancer [30][31][32], and DLEU2 has been reported related to the development of multiple cancers [33][34][35][36]. Chen et al reported that lncRNA DLEU2 could regulate miR-30a-5p and related to the aggressiveness of ccRCC [37].…”
Section: Discussionmentioning
confidence: 99%